Performing the aporias of the archive: Towards a future for South African music archives (Historia, 2021)
EnglishNational memory is continuously contested in South Africa and archives and museums are often called upon to store objects or material remnants of similarly contested pasts or histories. In addition, these institutions may already have collections that could be seen as contentious. If we consider these institutions as places where history is produced, what should be done with these objects and collections in a democratic country? This article provides a critical enquiry into the systems through which these objects are produced/recorded, appraised, catalogued and preserved as one methodology through which we can engage more fully with how these resources can be mobilised in the present. As a case study, the article will look at the International Library of African Music (ILAM), arguably one of the most important music archives in South Africa. The largest portion of ILAM’s holdings comprises field recordings collected by Hugh Tracey, a scholar who is both celebrated and contested. This paper proposes that through engaging with the processes and ambivalence inherent in Hugh Tracey’s recording and classification methods, ILAM has the capacity to provide critical and nuanced insight into one of the most important collections of music in southern-Africa.   AfrikaansIn Suid-Afrika, waar die nasionale geheue op ’n kontinue basis betwis word, word daar gereeld op argiewe en museums ’n beroep gedoen om objekte of materiële oorblyfsels van gekontesteerde verledes en geskiedenisse te berg. Boonop het argiewe reeds versamelings in hulle besit wat beskou kan word as omstrede. Indien ons hierdie instansies beskou as plekke waar geskiedenis geproduseer word, wat moet met hierdie objekte en versamelings gebeur in ’n demokratiese land? Hierdie artikel oorweeg die moontlikhede wat gebied word deur ’n kritiese ondersoek na die sisteme waardeur hierdie objekte geskep, beoordeel en gekatalogiseer en bewaar word, as een metodologie waardeur daar meer volledig omgegaan kan word met die wyses waarop hierdie bronne in die hede gemobiliseer kan word. As ’n gevallestudie, kyk hierdie artikel na die International Library of African Music (ILAM), een van die belangrikste musiekargiewe in die land. Die grootste deel van ILAM se versameling bestaan uit veldopnames wat gemaak is deur Hugh Tracey, ’n figuur wat beide gevier en betwis word. Die artikel stel voor dat, deur om te gaan met die prosesse en ambivalensie wat inherent deel van Hugh Tracey se opneem- en klassifikasie metodes was, ILAM oor die kapasiteit beskik om kritiese en genuanseerde insigte te lewer op een van die belangrikste versamelings van musiek in suidelike Afrika.
Keywords: Music archive; post-colonial discourse; International Library of African Music (ILAM); critical engagement; archival systems; cataloguing; classification; performance; Musiekargief; post-koloniale diskoers; kritiese navorsing; argiefsisteme; katalogisering; klassifikasie; performatiwiteit